1987
DOI: 10.1037/0022-006x.55.5.768
|View full text |Cite
|
Sign up to set email alerts
|

WISC—R verbal and performance IQ discrepancy in an unselected cohort: Clinical significance and longitudinal stability.

Abstract: This study examined children from an unselected birth cohort who had Wechsler Intelligence Scale for Children-Revised (WISC-R) verbal and performance IQ discrepancies that placed them beyond the 90th percentile. It was hypothesized that, relative to their cohort peers, these children would be characterized by greater frequency of perinatal difficulties, early childhood neurological abnormalities, health problems of neurological significance, and concussion. Additionally, it was hypothesized that such children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Yet, the less than desirable reliability of current factor-score comparisons makes it difficult to establish validity. Consistent with this, research has suggested that commonly used factor scores from commercial tests have had a disappointing track record, historically, in terms of demonstrating divergent, incremental, or predictive validity (Glutting, Youngstrom, Ward, Ward, & Hale, 1997;Moffitt & Silva, 1987). Yet, it is not clear whether these findings have resulted from poor measurement of additional factors (i.e.…”
Section: Validitymentioning
confidence: 96%
“…Yet, the less than desirable reliability of current factor-score comparisons makes it difficult to establish validity. Consistent with this, research has suggested that commonly used factor scores from commercial tests have had a disappointing track record, historically, in terms of demonstrating divergent, incremental, or predictive validity (Glutting, Youngstrom, Ward, Ward, & Hale, 1997;Moffitt & Silva, 1987). Yet, it is not clear whether these findings have resulted from poor measurement of additional factors (i.e.…”
Section: Validitymentioning
confidence: 96%
“…Based on Kaufman's suggestion mentioned above, Mof®t and Silva (46) examined clinical signi®cance and developmental course of large PIQ±VIQ discrepancy scores beyond the 90% percentile in a large unselected birth cohort in a longitudinal prospective study, known as the Dunedin Health and Developmental Study. In this investigation brain dysfunction as de®ned by nervous system insult history, early neurological abnormality, or perinatal problems were not more prevalent among children with PIQ±VIQ discrepancy beyond the 90% percentile (22±24 points or more) at the ages of 7, 9 and 11 years than in children without this discrepancy.…”
Section: Piq±viq Discrepancy In Normal Childrenmentioning
confidence: 99%
“…Percent with central nervous system syndromes. Moffitt and Silva (1987) have described in detail the procedures used for searching archives and designating neurological cases. Briefly, repeated medical and neurological examinations, setni-annual parental reports of illness and injury, and hospital emergency room records yielded documentation of relatively severe health problems consistent with a positive history of neurological disorder for 74 children in the sample.…”
Section: Appendix Amentioning
confidence: 99%